准双曲面齿轮设计分析集成软件系统的研究 - 李少华; 张金良; 方宗德 (Jixie Chuandong, 2007)
By the improving,developing and practicing during the last several years,the designing method of the machine-tool settings to the hypoid gear based on the local synthesis method has been shown that it is simple and precontrollable method.With the aid of the local synthesis method and HFT,the integration software systems of the design,manufacture and analysis for hypoid gear is researched and the composition of the integration software systems is presented.At last,an example is discussed and used to show the function of the integration software systems.